Caring for patients without being with them : invisibility of nursing care in hospitalization services (2018)
ABSTRACT: Objective: This work sought to understand the meaning of invisible care for nurses in hospitalization services. Methods: Qualitative ethnographic study conducted in Medellín, Colombia. Seven open interviews were conducted with an equal number of participants and 30 h of observation. The data was subjected to ethnographic analysis. Results: Two principal categories of analysis emerged: What nurses do and The transformation of the role; the latter with three subcategories (Priorities of the nurses: “What the nurse should do”, Priorities of the institutions: “That which has to be done”, Result of the change: “The unknown nurse”). Nurses during their daily work transform their caregiver role to adapt to diverse demands from the institutional contexts. If they do what they believe they should do, they are invisible to the institutions, but if they do what is visible to the institutions, care becomes invisible to patients and their relatives. Conclusion: In the hospitalization services, nurses care for patients but without being with them. Nurses during their daily work transformed their caregiver role to adapt to diverse demands from the contexts, especially the institutional context.